From promise to practice: CAR T and Treg cell therapies in autoimmunity and other immune-mediated diseases - Bulliard, Yannick; Freeborn, Robert; Uyeda, Molly Javier; Humes, Daryl; Bjordahl, Ryan; de Vries, David; Roncarolo, Maria Grazia (Frontiers in Immunology, 2024)
Autoimmune diseases, characterized by the immune system’s attack on the body’s own tissues, affect millions of people worldwide. Current treatments, which primarily rely on broad immunosuppression and symptom management, are often associated with significant adverse effects and necessitate lifelong therapy. This review explores the next generation of therapies for immune-mediated diseases, including chimeric antigen receptor (CAR) T cell and regulatory T cell (Treg)-based approaches, which offer the prospect of targeted, durable disease remission. Notably, we highlight the emergence of CD19-targeted CAR T cell therapies, and their ability to drive sustained remission in B cell-mediated autoimmune diseases, suggesting a possible paradigm shift. Further, we discuss the therapeutic potential of Type 1 and FOXP3+ Treg and CAR-Treg cells, which aim to achieve localized immune modulation by targeting their activity to specific tissues or cell types, thereby minimizing the risk of generalized immunosuppression. By examining the latest advances in this rapidly evolving field, we underscore the potential of these innovative cell therapies to address the unmet need for long-term remission and potential tolerance induction in individuals with autoimmune and immune-mediated diseases.